Assessing the Diagnostic Accuracy of C-Reactive Protein (CRP) in Neonatal Sepsis Detection - Saud Salman Al-Atwi, Mona Awad Al-Atwi, Muhammad Salem Al-Balawi , Munawar Khader Al-Balawi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The purpose of this study was to evaluate how well C-reactive protein (CRP) levels diagnose newborn sepsis.Methods: At the KRL General Hospital's Neonatology unit, a validation study was carried out over the course of seven months, from February to August 2012. Using purposive sampling, a sample size of 147 neonates was established based on a 95% confidence level, 50% predicted prevalence, 75% sensitivity, 95% specificity, and 10% desired accuracy.Results: The neonates' mean age was 5.72 days ± 3.86. Of the patients, 81 (55.1%) were male and 66 (44.9%) were female. Through blood culture, 43 neonates (29.25%) had neonatal sepsis confirmed, whereas 104 neonates (70.75%) did not test positive for the condition. When it came to identifying acute neonatal sepsis, CRP's sensitivity and specificity were 76.92% and 53.49%, respectively. 48.94% was the negative predictive value and 80% was the positive predictive value. In terms of identifying neonatal sepsis, CRP had an overall diagnosis accuracy of 70.07%.Conclusion: Although it lacks specificity, CRP estimation can be helpful in identifying newborn sepsis; nevertheless, it should not be the only method used.